2020
DOI: 10.1371/journal.ppat.1008792
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 38 alters wild-type p53 activity to promote cell proliferation via the downregulation of integrin alpha 1 expression

Abstract: Tumor suppressors can exert pro-proliferation functions in specific contexts. In the beta human papillomavirus type 38 (HPV38) experimental model, the viral proteins E6 and E7 promote accumulation of a wild-type (WT) p53 form in human keratinocytes (HKs), promoting cellular proliferation. Inactivation of p53 by different means strongly decreases the proliferation of HPV38 E6/E7 HKs. This p53 form is phosphorylated at S392 by the double-stranded RNA-dependent protein kinase PKR, which is highly activated by HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 51 publications
(79 reference statements)
1
18
0
Order By: Relevance
“…A 2.44-fold increase in the expression of the ITGB5 gene, which encodes the β5 integrin subunit, was reported in cervical cells upon L2 overexpression [ 19 ]. In contrast, it was reported that HPV38 E6/E7 proteins downregulate the expression of αvβ8 integrin in human keratinocytes [ 20 ].…”
Section: Human Papillomavirus and Epstein–barr Virus Tropismmentioning
confidence: 99%
“…A 2.44-fold increase in the expression of the ITGB5 gene, which encodes the β5 integrin subunit, was reported in cervical cells upon L2 overexpression [ 19 ]. In contrast, it was reported that HPV38 E6/E7 proteins downregulate the expression of αvβ8 integrin in human keratinocytes [ 20 ].…”
Section: Human Papillomavirus and Epstein–barr Virus Tropismmentioning
confidence: 99%
“…Cells were lysed in modified RIPA buffer (10 mM Tris-HCl, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1% Igepal). Immunoprecipitation (IP) experiments were performed as previ-ously described [50,51]. Briefly, cells were lysed in RIPA buffer (50 mM Tris-HCl, pH 8.0, 150 mM NaCl, 1 mM EDTA, 1% Igepal, 0.5% sodium deoxycholate).…”
Section: Immunoprecipitation and Western Blottingmentioning
confidence: 99%
“…Transgenic animal models for the cutaneous HPV8 and HPV38 associated with cancer in EV patients have documented the carcinogenic activities of these HPVs [ 21 , 22 , 23 , 24 , 31 , 32 , 33 , 34 ]. Transgenic mice that express the complete early region of HPV8 expressed from the K14 promoter spontaneously develop papillomas at a high frequency that progressed to cutaneous squamous cell carcinoma (cSCC) in a subset of these mice [ 21 ].…”
Section: Animal Models For Studying Oncogenic Activities Of Pvsmentioning
confidence: 99%
“…The cutaneous, beta and gamma HPVs lack E5 genes. The E6 and E7 proteins of some cutaneous HPVs have been demonstrated to display oncogenic activities in cell and transgenic animal-based studies [ 16 , 21 , 22 , 23 , 24 , 25 , 26 , 30 , 31 , 32 , 33 , 34 , 35 ]. Because of the pronounced species specificity of papillomaviruses, it has not been possible to perform pathogenesis studies by experimentally infecting laboratory animal with HPVs.…”
Section: Introductionmentioning
confidence: 99%